Pengaruh Dukungan Suami dan Nilai-Nilai Spiritualitas terhadap Depresi Ibu Pasca Melahirkan di Wilayah Kerja Puskesmas Rembang Kabupaten Purbalingga - Dina Praktika Rosyada; Tutik Rahayu; Sri Wahyuni (Jurnal Ventilator, 2025)
Husband support and spiritual values are very useful to accelerate recovery and can reduce the risk of complications during pregnancy or other postpartum problems such as postpartum depression in the mother. The purpose of this study is to find out the influence of husband support and spirituality values on postpartum maternal depression. This research is a type of quantitative research with a cross-sectional approach. The sample used was postpartum mothers on the 3rd - 2nd day postpartum in the work area of the Rembang Health Center. The number of respondents in this study amounted to 85 people with the technique used being total sampling. The data obtained were processed statistically using the sommers'd correlation test. The results of this study show that the majority of respondents at the age of risk are 67.1%, the majority of mothers' education is at the high school/vocational education level as much as 48.2%, the majority of mothers' employment as IRT is 71.8%, the majority of children owned by mothers are 1 child as much as 50.6%, mothers who get the support of supportive husbands as much as 91.8%, mothers who have high spiritual value as many as 95.3%, and mothers who do not experience depression (normal) as many as 38.8%. the results of the test of the relationship between husband support and postpartum maternal depression using the Somers'd test obtained a value of p = 0.003 (p < 0.05) and a value of r = 0.795 (0.60 – 0.799), the results of the test of the relationship of spiritual value to postpartum maternal depression using the Somers'd test obtained a value of p = 0.032 (p < 0.05) and a value of r = 0.827 (0.80 – 1.00), The results of the multivariate test of husband support and spiritual value on maternal depression using a multiple linear regression test on husband support obtained a value of p = 0.007 (p < 0.05) so that it can be concluded that husband support is the dominant factor influencing maternal depression. In conclusion , there is an influence of meaningful relationships with husband support and spiritual values on postpartum maternal depression.